Dietary Phospholipids Requirement for Beluga Sturgeon (Huso huso) Juveniles - Ebrahimnezhadarabi, Mahmoudreza (2010)
A study was carried out to determine the influence of dietary phospholipids (PL) levels on growth, body composition, haematology parameters, biochemical factors and immune parameters of beluga sturgeon (Huso huso) juveniles. Juveniles were fed formulated diet with four varying dietary levels of PL i.e. 0 (D1), 2 (D2), 4 (D3), and 6% (D4). At the end of the experimental period (56 days), the results showed that there were significant differences (P<0.5) among treatments in growth performance. Fish fed diet containing 4% phospholipids obtained the best weight gain and percentage survival (P<0.05) with values of 70.3 g and 76.7% respectively. However, there was no significant difference (P>0.05) was found for feed conversion ratio (FCR), specific growth rate (SGR), protein efficiency ratio (PER), and lipid efficiency ratio (LER). Significant differences (P<0.05) were observed in moisture and protein composition in fish among all treatments but however, the inclusion of phospholipids in diets had no significant effect (P>0.05) on the fat and ash composition in fish. Results of the experiment also showed that there was a significant difference (P<0.05) observed in mean corpuscular hemoglobin concentration (MCHC) (g/dl). Fish fed diet D2 (2% PL) had the highest MCHC with a value of 33.3 g/dl. There was no significant different (P>0.05) in other haematology parameters such as red blood cells (RBC), haematocrit (Hct), haemoglobin (Hb), mean corpuscular hemoglobin (MCH), mean corpuscular volume (MCV), and white blood cells (WBC) in treated fish . The highest RBC reading was found in fish fed diet D2 with numerical value of 1.07 (cells/l) for and the lowest value was found for fish fed diet D1 with a value of 0.86 (cells/l). Percent haematocrit readings ranged from the highest (fish fed D3) to the lowest (fish fed D1) with values of 26.33 and 25.00% respectively. Haemoglobin (Hb) ranging from the highest (fish fed D2) to the lowest (fish fed D1) with values of 8.64 and 7.67 (g/dl) respectively. Mean corpuscular hemoglobin (MCH) ranging from the highest (fish D1) to the lowest (fish fed D2) with values of 92.57 and 77.27 (pg/cell) respectively. Mean corpuscular volume (MCV) ranged from the highest (fish fed D1) lowest (fish fed D2) with values of 300.83 and 232.60 (fL/cell) respectively. White blood cells (WBC) count in fish fed with varying dietary phospholipids levels, ranged from the highest (fish fed D2) lowest (fish fed D3) with values 25866.67 and 22633.33 (cell/μl) respectively. The measurement of differentiated white blood cell of Huso huso with varying dietary phospholipids levels such as lymphocytes, monocytes, neutrophils, and eosinophils also showed that there were no significant differences (P>0.05) amongst the treatments. The highest percentage amount of lymphocyte and monocyte were found in fish fed diet D2 with values of 71.67% and 3.67% respectively. While the highest readings for neutrophils, and eosinophils was found in fish fed diets D1 and D4 with values of 21.33% and 8.33% respectively. The lowest amount of lymphocyte, neutrophil, monocyte, and eosinophils were shown in fish fed diets D4, D2, D3, and D1 with values of 68, 18.67, 2.33 and 6% respectively. At the end of the experimental period, there were no significant differences (P>0.05) were found for hepatic enzymes among treatments. The enzyme alanine aminotransferase (ALT) was highest in fish fed diet D2 while the lowest was found in fish fed diet D1 with values of 46.07 and 24.70 (IU/L) respectively. The enzyme aspartate aminotransferase (AST) was found highest in fish fed diet D3 and lowest was found in fish fed diet D2 with values 16.43 and 12.47 (IU/L) respectively. The enzyme lipase was found to be highest in fish fed diet D4 while the lowest was shown in fish fed diet D3 with values of 32.47 and 29.03 (IU/L) respectively. Among the biochemical factors, there was a significant difference (P<0.05) observed in blood sugar, the highest reading was found in fish fed diet D3 with amount of 83 mg/dl and the lowest amount was found in fish fed diet D2 with a value of 46 mg/dl. However, the other biochemical parameters such as cholesterol and triglyceride did not showed significant differences (P>0.05) among treatments. The triglyceride values ranged from the highest and lowest values were found in fish fed diets D4 and D2 with values of 349.33and 263.00 (mg/dl) respectively. The cholesterol values ranged from the highest and lowest were found in fish fed diets D4 and D2 with values of 121.67and 104.67 (mg/dl) respectively. Among the immunological parameters, a significant difference (P<0.05) was observed in the third component of complement in immune system (C3) where the highest reading was observed in fish fed diet D4 and lowest found in fish fed diet D3 with values of 7.50 and 5.83 (mg/dl) respectively. But as for the other immunological parameters which are the fourth component of complement in immune system (C4), the alternative component of complement in immune system (CH50) and Immunoglobulin molecule consisting (IgM), showed no significant among treatments of different levels of phospholipids (P>0.05). The amount of C4 was highest in fish fed diet D1 and lowest was shown fish fed diet D4 with values of 4.33 and 3.10 (mg/dl) respectively. The content of CH50 was highest in fish fed diet D3 and the lowest was shown in fish fed diet D1 with values of 30.00 and 25.40 (mg/dl) respectively. The immunoglobulin molecule (IgM) ranged from the highest and lowest was shown in fish fed diets D3 and D2 with values of 4.10and 3.10 (mg/dl) respectively. In conclusion, the addition of 4% phospholipids in the juvenile’s beluga sturgeon diet can increase growth performances.